Prevalência e fatores associados á síndrome de Burnout em médicos dos hospitais de Francisco Beltrão – Paraná - Becker, Natalia Dalla Costa (2020)
Burnout Syndrome derives from professional experience in a milieu with numerous emotional stressors and complex social relationships, a result of the relation between the professional and his workplace. It presents itself in three dimensions: Emotional Exhaustion, Depersonalization and Sense of Personal Accomplishment. The most predisposed professions to the development of Burnout Syndrome are those whose activities encompass emotional involvement, such as professionals who work directly with other people, assisting them, or as responsible for development and well-being. A professional career that is particularly susceptible to develop Burnout Syndrome is that of the physician, consisting of a highly prevalent phenomenon amongst these professionals. The present study aimed to estimate the prevalence and identify factors associated with Burnout Syndrome in doctors at the hospitals of Francisco Beltrão - Paraná, as well as outline the profile of these professionals; evaluate the levels of Emotional Exhaustion, Depersonalization and Personal Accomplishment; identify the relationship between Burnout and sociodemographic, occupational and psychosocial characteristics, and describe the characteristics of professionals with Burnout Syndrome. This is a descriptive and quantitative research comprising 121 physicians who work in hospitals in the municipality of Francisco Beltrão - Paraná. The Maslach Burnout Inventory and a sociodemographic questionnaire were the instruments used to collect the data. The data analysis showed that the majority of the participants are male, married, with children, work on call and are satisfied with the institution where they work. Approximately half of them reported working more than 70h / week and not going on vacation in the last six months. The frequency of diagnosis of psychological disorder, consumption of anxiolytics, regular psychiatric appointments and intention to change profession varied between 20% and 25%. High levels of Emotional Exhaustion, Depersonalization and low Personal Accomplishment were found in 33.9%, 31.4% and 20.8% of respondents, respectively. The prevalence of high-level intensity in the three dimensions was 7.5%. The lowest values of Emotional Exhaustion were observed amongst the senior; those with workload between 40 and 60 hours; who do not work on call; who exercise regularly; who went on vacation in the last six months; those satisfied with the institution; with no diagnosis of psychological disorders; who don’t have regular appointments with a psychiatrist; and who do not consider changing their profession. Those who work longer hours, who attend more than 25 patients a day, who are dissatisfied with the institution and considering changing their profession showed higher Depersonalization values. Higher values of Personal Accomplishment were observed among participants with lesser weekly workload, non-outsourced workers, who do not work on call, who exercise regularly, who went on vacation less than six months ago, who are satisfied with the institution, who don’t consider changing their profession. Lastly, better indicators of the general score of Burnout Syndrome were observed in those with less workload, who exercise regularly, who went on vacation less than six months ago, who are satisfied with the institution, who have no diagnosis of psychological disorder, who have not had regular psychiatric appointments and who do not consider changing their profession.